Indian Society of Vascular and Interventional Radiology Expert Consensus Statements for Ablation in Hepatocellular Carcinoma: Part II - Pankaj Gupta; Shyamkumar N. Keshava; Naveen Kalra; Sreedhara B. Chaluvashetty; Amar Mukund; Shuvro H. Roy-Choudhury; Sanjay Saran Baijal; Anubhav Khandelwal; Venkatesh Hosur Ananthashayana; Sathya Narayanan R.; Suyash S. Kulkarni; Nitin Sudhakar Shetty; et al. (Journal of Clinical Interventional Radiology ISVIR)
Locoregional therapies play an important role in the management of hepatocellular carcinoma (HCC). Percutaneous ablation is one of the most commonly employed nonsurgical methods for treating very early and early HCC. For small HCC, ablation is potentially curative and competes with surgical resection. The widespread availability and the spectrum of ablative techniques mandate uniform approach among interventional radiologists. Thus, it is desirable to have a consensus regarding various aspects of the liver ablation. This article represents a consensus document of the experts from the Indian Society of Vascular and Interventional Radiology involved in the care of patients with HCC. The statements are presented in two parts.